Analysis of lexical richness three book genres based on MSTTR - Atikah Solihah; Harini Harini (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
Lexical richness is one indicator of vocabulary diversity in a text and is important to study in order to understand the characteristics of language across various genres. However, to date, comparisons of lexical richness across books of different genres have been limited. Therefore, this study aims to compare the lexical richness of three Indonesian-language books, namely Visi Anak Pasar, Yang Fana Adalah Waktu, and Tata Bahasa Baku Bahasa Indonesia, using the Mean Segmental Type-Token Ratio (MSTTR) based on lexical richness theory. This study was conducted using a mixed-methods approach, combining quantitative and qualitative methods. The quantitative approach was carried out using an explanatory technique with the MSTTR instrument. Meanwhile, the qualitative approach was carried out using corpus analysis techniques, including frequency analysis using a concordance plot, morphological analysis, and contextual analysis using the Leipzig-Corpora corpus. The results of the study show that the autobiography Visi Anak Pasar has the highest average MSTTR value, at 51.5 per cent, followed by the novel Yang Fana Adalah Waktu’ at 45.9 per cent, whilst the book Tata Bahasa Baku Bahasa Indonesia has the lowest average MSTTR value, at 39 per cent. These findings suggest that the personal narrative genre exhibits a higher tendency for lexical repetition compared to the other two books. Consequently, MSTTR can be used as a tool for comparing lexical characteristics across genres in a more balanced manner. Keywords: Lexical richness; Mean Segmental Type–Token Ratio (MSTTR); texs genre.